Evaluating early‐age shrinkage effects in steel concrete composite beam‐like structures. Issue 1 (January 2017) - Li, Xi; Glisic, Branko
Abstract: Dedicated to Prof. Dr. Akimitsu Kurita on his 70th birthday The shrinkage of concrete is a material phenomenon that occurs due to the reduction in the concrete's volume over time. In composite beam‐like structures, the shrinkage of concrete elements affects strains and stresses in the overall composite section. The ability to identify and estimate early‐age shrinkage in beam‐like structures allows the creation of a baseline for strain‐based structural health monitoring, and enables a more thorough understanding of structural performance and condition. In this project, the early‐age shrinkage behaviour of steel‐concrete composite beam structures was studied with an integrated approach using monitoring data from a reduced‐scale test structure and simulation results from finite element analysis. A simplified analytical expression was developed to study further the range of magnitude of shrinkage in the concrete slab and the resultant strain distribution in steel girders. The goal of this paper is to create an innovative, comprehensive and widely applicable procedure that identifies and quantifies early‐age shrinkage in steel‐concrete composite beam‐like structures and its effects on the overall composite cross‐section.